Green bonds : an introduction to a new market based approach in solving the regional haze crisis - Chew, John Han Hui (2015)
In 1997, several important industries in Singapore were adversely affected by the uncontrolled burning of farmland in Indonesia which caused the region to be engulfed in haze. Since then, following greater pressure from its ASEAN neighbours, Indonesia has made greater efforts in attempting to curb the problem through stricter regulations. However, the extent of success of these measures has been limited as evidenced from the recurrence of the haze problem over the years; most recently in 2013. Given tighter rules and regulations do exist, our group seeks to critically examine these measures to tackle the haze problem and explain underlying factors behind their ineffectiveness. We performed a cost benefit analysis for Singapore‟s tourism and health industries, two key industries most affected by the haze. Damages in terms of direct costs incurred as well as lost opportunity costs were measured using appropriate cost approximation methodologies. A cross-comparison against the PSI ascertained the financial impact of the haze crisis. Our results showed that the projected relationships between damages to the tourism sector and PSI levels were harder to prove. This could potentially be due to limitations such as time lags between the haze and travelling. In contrast, there was a stronger relationship demonstrated between the health sector and PSI levels. Green Bonds and its growing successes in resolving environmental issues worldwide has motivated our group to explore how they could be used as a means to resolve the haze issue. Our paper explores the rationale for using Green Bonds over financial aid as well as explaining the details of the whole Green Bonds issuance process. Our proposal for the Singapore Government to take lead in the issuance process is primarily due to Singapore‟s strong reputation as a clean, efficient and well connected financial hub and the inertia of neighbouring countries to take the lead.